Zakat Harta dari Hasil Undian Berhadiah dalam Perspektif Hukum Islam - Muhammad Taufan Djafri; Patahuddin , Askar; Aqbar, Khaerul; Syarifuddin, Chaeril (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This study aims to determine the law and position of the lottery results from prizes, and to know the zakat property laws from lottery results. This study uses a qualitative library method with deductive data analysis. The research results found are as follows; First, the lottery law in Islamic law may be based on the proposition which explains that the Messenger of Allah. had done the lottery, so did the argument that explained that the Prophet Yunus had been thrown from a ship after the draw, and in general there was no argument that explained the forbidden draw. The position of the property from the lottery results is halal. Secondly, the law of issuing zakat assets from the lottery results is mandatory if the assets obtained from the lottery results do not overlap with Islamic law, for example in the category of goods that are not required to pay zakat, such as houses, land, vehicles and remain in accordance with the reckoning of the lottery results. If the gift has reached the Nisab, the zakat must apply in accordance with the provisions of gold and silver and also haul (held for a year), because this asset has become his property as a gift, which when he receives it becomes his property and is intended to be traded, this provision applies to lottery proceeds in the form of gold, silver and cash, while the rest is returned to the intention of the recipient of the prize, if he does not want to sell but only to be used, then the law that applies to the lottery results is not obligatory zakat.